2008
DOI: 10.2174/138920108783497631
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9/Gelatinase B is a Putative Therapeutic Target of Chronic Obstructive Pulmonary Disease and Multiple Sclerosis

Abstract: Matrix metalloproteinases (MMPs) are a large family of proteolytic enzymes involved in an array of physiological and pathological processes from development, morphogenesis, reproduction, wound healing, and aging to inflammation, angiogenesis, neurological disorders, and cancer cell invasion and metastasis. The imbalance between MMP activity and the inhibitory action of tissue inhibitors of metalloproteinases (TIMPs) are implicated in multiple diseases. Secreted in the body in a latent form, upon activation MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(30 citation statements)
references
References 121 publications
(139 reference statements)
0
30
0
Order By: Relevance
“…This implies that the inhibitors of MMP-9 have potential to impede the development of retinopathy in diabetic patients. Optimistically, these inhibitors are being used in clinical trials for other diseases, including chronic obstructive pulmonary disease and multiple sclerosis (23). …”
Section: Discussionmentioning
confidence: 99%
“…This implies that the inhibitors of MMP-9 have potential to impede the development of retinopathy in diabetic patients. Optimistically, these inhibitors are being used in clinical trials for other diseases, including chronic obstructive pulmonary disease and multiple sclerosis (23). …”
Section: Discussionmentioning
confidence: 99%
“…A marked increase in COX-2 expression was observed in alveolar macrophages, as well as in alveolar epithelial cells following NM exposure. MMP-9 is a matrix metalloproteinase produced by proinflammatory/cytotoxic macrophages and is important in tissue injury and remodeling (Muroski et al, 2008). We found that MMP-9 was upregulated in lung macrophages after NM exposure (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α-stimulated NF-ÎșB activation induces the expression of MMP-9, a potential drug target for treatment of COPD (Muroski et al, 2008). We therefore tested whether indacaterol, which inhibits TNF-α-stimulated NF-ÎșB signaling, also down-regulates the expression of MMP-9.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown MMP-9 to be a potential drug target for COPD (Muroski et al, 2008), since overexpression of MMP-9 is correlated with lung damage (Chetty et al, 2008), while selective inhibition of MMP-9 prevents smoke-induced increase in small airway wall thickness in a guinea pig model (Churg et al, 2007). Therefore, we investigated whether MMP-9 expression and enzymatic activity are regulated by indacaterol in human fibrosarcoma (HT1080), which express MMP-9 in abundance.…”
Section: Discussionmentioning
confidence: 99%